Praktik Digital Marketing Melalui Pelatihan Pembuatan Website Untuk Meningkatkan Hasil Produk Warga Binaan Lembaga Pemasyarakatan - Ika Zutiasari; Dede Rusmana; Fitrotul Isnaini; Noval Arkan Abiyyi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The Class IIA Women's Correctional Institution (LPP) in Malang City is included in a productive prison which is not only used as a place for fostering prisoners (inmates), but also used as a facility to accommodate the production of quality prisoner products. The WBP participates in productive program activities held by the prison, such as managing the soy sauce industry, handicrafts, convection business, salon business, making ecoprint batik, production of souvenir snacks. All WBPs are involved in these productive activities as a form of effort by the prison in organizing work guidance programs and skills education. The results of the activity show that the production of Malang City Class IIA Women's Prison can be said to be quite good and has selling value. However, it is unfortunate that marketing is done conventionally so that it has not achieved maximum product sales results. Therefore, it is necessary to have an evaluation that can be solved through the service activities carried out. This digital marketing practice activity with website development training can be a solution provided through this service. The activity can run smoothly because all prison officers are enthusiastic and conducive in participating in the training held. The hope of this activity is that they will be able to apply the marketing function optimally so that it can increase sales volume